Amparo Constitucional a Enfermedades Catastróficas, o Vulneración del Derecho a la Salud y del Derecho a la Vida - Ruiz Ramón, María Augusta (2018)
The present thesis focuses on the problem that refers to the treatment that can be to catastrophic patients, and, especially, to the access of medicines that these patients can not have at least to be acquired by the State, even though the articles 35 and 50 of the Constitution speaks of priority, specialized and free attention. Question that is also offered in the Organic Law of Health, the same as in its article 1 of the chapter of catastrophic, rare or orphan diseases states that the treatment of these diseases is treated. Having established the previous legal guarantee, this research is based on the study of the need for drugs and devices for catastrophic diseases, looking for ways to provide a sustainable solution to this socio-legal dilemma. Taking into account historical information, conceptualizations, regulations and doctrine, such as the application of surveys and interviews, dissemination of specific theories on the legal aspect of catastrophic diseases, which are clearly and precisely based; in addition to specialized bibliography. All these media collaborated with the verification of objectives and testing of the proposed hypothesis of the legal problem, established in the Constitution, in the Organic Law of Health and the related laws that have established the rights for this group of priority attention and the main rights to health and the right to life.